PENINGKATAN KEPATUHAN WAJIB PAJAK DALAM PEMBUATAN NPWP UKM DI KEBUN LADA KECAMATAN HINAI KABUPATEN LANGKAT - Yunita Sari Rioni; Junawan Junawan; Roro Rian Agustin (Jurnal Abdi Ilmu, 2021)
This service aims to help SMEs in Lada Gardens, Hinai District, Langkat Regency so that they can understand how to make NPWP, provide understanding to become taxpayers who comply with the applicable Taxation Law. In SMEs, it is very necessary to have a TIN, from the socialization carried out to SMEs in the Pepper Garden, Hinai District, Langkat Regency, the perpetrators understand the making of SME TIN and understand being a good taxpayer.